Edukasi Teknik Perendaman Benih Kerang Mutiara Pinctada maxima Dalam Bak Pakan Alami Untuk Meningkatkan Pertumbuhan Benih: Program Pengabdian Masyarakat Di Desa Sugian, Lombok Timur - Nunik Cokrowati; Wastu Ayu Diamahesa; Sahrul Alim; Laily Fitriani Mulyani; Alis Mukhlis (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The cultivation of pearl oysters Pinctada maxima is an important economic sector in Indonesia, but its productivity is often hampered by low growth rates and spat survival. This community service program aims to educate pearl oyster farmers in Sugian Village, East Lombok, Indonesia, through training on spat immersion techniques in natural feed tanks to improve growth. The implementation method includes theoretical and practical training for two days (August 24-25, 2024) with a community-based participatory approach, involving 20 members of active pearl oyster farming groups operating in the waters around Sugian Village. This program is supported by PT. Mutiara Surya Indonesia, a national pearl oyster cultivation company operating in Sugian village. The training materials cover pearl oyster biology, spat nutrition principles, natural feed culture techniques, immersion methods, and growth monitoring. Evaluation results show that all participants expressed that this technology is greatly needed by the community to increase cultivation productivity. The main challenges identified are the need for initial capital and access to microalgae cultures. As a follow-up, it is recommended to provide training on household-scale microalgae natural feed culture that applies simple technology, easy to understand and apply by pearl oyster farming communities. This program has the potential to increase productivity and income of local farmers. Moreover, the technology presented has prospects to be developed and replicated in other regions of Indonesia.